Campus Sexual Violence Victims with Disabilities: Disclosure and Help Seeking - Kirkner, Anne (Journal of interpersonal violence, 2022)
Undergraduate students with disabilities represent an important population on college campuses. Yet the incidence of sexual violence and disclosing/reporting of sexual violence among this population is understudied. This exploratory and largely descriptive study uses an intersectional framework to understand the sexual victimization of undergraduate students with disabilities at a large Mid-Atlantic academic institution. The sample consisted of students who completed a sexual violence module (N = 2,929) as part of a larger campus climate survey. Students with disabilities comprised a smaller sample within this group (n = 177) and descriptive and chi-square results from both groups of students are reported. Students with disabilities had a statistically significant higher likelihood of sexual violence victimization before coming to campus and while at the university, with much higher rates for precollege victimization than students with no disabilities. Disclosure rates were not different for students across the two groups, though students with disabilities were more likely to utilize formal sources of support, such as campus Title IX offices and mental health services. This study shows support for a strengths-based approach that recognizes that students with disabilities may be more likely to reach out to campus resources. The findings of the study also underscore the need for culturally relevant victim services for students with disabilities. An evaluation of the culture of a university and its environment of openness, sharing, community, and protection (or lack thereof) can be a key point for future approaches to sexual violence on campus.